The value of aspiration biopsy in endometrium assessment - Malinowski, Andrzej; Bartosiak, Ilona; Cieślak, Jarosław; Obuchowska, Lila; Woźniak, Piotr; Augustyniak, Tomasz; Pietrzak, Zbigniew (Menopause Review/Przegląd Menopauzalny, 2003)
Objective: The results of histopathological examination of endometrium sampled using pipelle de Cornier and fractioned curettage were compared. All samples were collected after the hysteroscopic examination cavity. Material and methods: Two hundred and four women that were hospitalized in the Gynecologic Division of Polish Mother’s Memorial Hospital – Research Institute were involved in the study. The age of this population was in the range of 41–73 years. In every case a thorough ultrasonographical assessment of endometrium was performed and hysteroscopy, traditional curettage and endometrial aspiration biopsy with pipelle de Cornier were performed afterwards. The results of histopathological examination of endometrium obtained during biopsy and curettage were compared. Results: Endometrial biopsy had the sensitivity and specificity of 100% for detecting endometrial cancer and endometrial non-atypical hyperplasia. The detection of endometrial polyp had the lowest sensitivity (33.3%) and detection of endometritis the lowest specificity (85.7%). Conclusions: Aspiration biopsy of endometrium with pipelle de Cornier is an accurate, painless, easily performed and cheap method in examination of endometrium.